1977
DOI: 10.1107/s0567740877005834
|View full text |Cite
|
Sign up to set email alerts
|

The hydrogen bonding of hydromagnesite

Abstract: Abstract. Mgs(CO3)4(OH)2(H20)4 (Dovez, Iran), monoclinic, P21/c , a = 10.105 (5), b = 8.954 (2), c = 8.378 (4)/I,, fi = 114.44 (5) °, Z = 2, Dr~ (flotation) = 2.25, Dx = 2.25 g cm -3. The H positions have been determined from three-dimensional X-ray data. The H atoms in the water molecules take part in a hydrogenbond system, while those in the hydroxyl groups do not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
84
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(89 citation statements)
references
References 3 publications
5
84
0
Order By: Relevance
“…Changes in the carbonate FTIR spectra showed that there was interaction between these groups and the water molecules as they realigned themselves into the crystal structure. This may well have been due to hydrogen bonding of the water molecules to the carbonate groups as discussed by Akao [45].…”
Section: Comparison Of Synthetic Hydromagnesite With Naturally Occurrmentioning
confidence: 99%
See 3 more Smart Citations
“…Changes in the carbonate FTIR spectra showed that there was interaction between these groups and the water molecules as they realigned themselves into the crystal structure. This may well have been due to hydrogen bonding of the water molecules to the carbonate groups as discussed by Akao [45].…”
Section: Comparison Of Synthetic Hydromagnesite With Naturally Occurrmentioning
confidence: 99%
“…The strong C-O bonds of the carbonate ion reinforce the crystal by forming a triangular structure with three oxygen atoms from three different octahedra. In a subsequent publication [45] in 1977 Akao further developed understanding of the structure by determining in greater detail the positions of the remaining water molecules and the hydroxyl group. The hydroxyl group was shown to be shared between three MgO 6 octahedra and does not take part in any hydrogen bonding, while the water molecules are located at unshared corners of the MgO 6 octahedron and form a network of hydrogen bonds.…”
Section: Chemical Formula and Crystal Structure Of Hydromagnesitementioning
confidence: 99%
See 2 more Smart Citations
“…There has been much work published regarding the structure [18][19][20][21][22][23] and thermal decomposition [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] of hydromagnesite and huntite. A recent article [40], by the current authors, reviews this body of work in detail.…”
Section: Hydromagnesite and Huntite As Fire Retardant Additivesmentioning
confidence: 99%